PENGARUH KONTROL DIRI TERHADAP PERILAKU KONSUMTIF PENGGUNA APLIKASI BELANJA ONLINE MAHASISWA FASHON DESIGN - Vira Krisnayanti, Ni Putu; Ratih Andhini, Luh Putu; Noviana Utami, Ni Made Sintya (Psikologi Prima, 2023)
Nowadays, technology is developing very quickly and bringing many changes to how people live, especially in buying and selling. This certainly influences students in consumptive behavior. It is not uncommon for students to have a habit of buying something based on desire alone, so it is hoped that students have both behavioral and cognitive self-control to prioritize needs over desires. The study aimed to determine whether self-control influences the consumptive behavior of online shopping application users in fashion design students. This research was conducted with simple linear regression statistical analysis. The subjects in the study were 96 fashion design students. The measuring instrument for this study is the self-control scale previously used by Dzihan (2020) and the consumptive behavior scale developed by Dzihan (2020). The results showed that self-control influences the consumptive behavior of online shopping application users in Fashion design students, with a significant value of 0.000 and an R-value of 0.543. Self-control contributed 28.5%. A total of 48 students have high consumptive behavior, and 79 students have moderate self-control. Based on the data obtained, it can be concluded that self-control influences a person's consumptive behavior. However, there are still several aspects that influence student consumptive behavior. It is hoped that further research can expand and develop other actors to be studied.